Karakteristik Kimia dan Kualitas Organoleptik Cokelat Pasta Dengan Suhu Penyangraian Yang Berbeda Menggunakan Alat Coffee Roasting - Marpaung, Ridawati; Hartawan, Rudi; Lesinde Simatupang, Oliviandra Afrianda (Jurnal Media Pertanian, 2024)
The aims of this research were to determine the chemical characteristics and organoleptic quality of chocolate paste with different roasting temperatures using a coffee roasting tool. The environmental design used in this study was a Completely Randomized Design Treatment design, namely different roasting temperatures, with 4 roasting temperature levels, as follows: t1 (130oC) ; t2 (140oC); t3 (150oC );Â  and t4 (160oC). The duration of roasting was carried out for 30 minutes. Each treatment was repeated 3 times so that there were 12 experimental units. The variables observed in this study were chemical characteristics including water content dry cocoa beans, acidity (pH) and fat content of roasted cocoa beans, while the organoleptic qualities observed were: color, aroma, taste, bitterness, and preference for chocolate paste. The The results showed that: different roasting temperatures have a significant effect on the fat content of the roasted cocoa beans, but are not significantly different on the pH of the roasted cocoa beans : color, aroma, taste, bitterness and preference for chocolate paste. The sensory test showed that panelistsÂ  preferred aroma, preferred taste, level of bitterness was slightly bitter and level of preference was liked were 130oC-160oC.